Incomplete interval type-2 fuzzy preference relations based on a multi-criteria group decision-making model for the evaluation of wastewater treatment technologies. (February 2020) - Yao, Liming; Xu, Zhongwen; Lv, Chengwei; Hashim, Muhammad
Highlights: We develop a decision-making framework to evaluate wastewater treatment technology. Opinions of experts and local residents are integrated in the framework. Different wastewater treatment technologies are suitable for different contexts. The decision-making framework eases the burden of decision makers. Interval Type-2 fuzzy sets are used to manage the complexity of the process. Abstract: Water pollution is a problem globally, where untreated human and industrial waste is directly discharged into water bodies. Choosing a suitable wastewater treatment technology (WTT) is vital. We develop a novel multi-criteria group decision-making framework to evaluate four WTTs (Anaerobic Anoxic Oxic, Triple Oxidation Ditch, Anaerobic Single Oxidation Ditch, Sequencing Batch Reactor Activated Sludge). It consists of four phases: (1) collecting incomplete linguistic pairwise comparisons; (2) characterizing this matrix by incomplete interval type-2 fuzzy sets; (3) repairing incomplete information to reach predefined consistency/consensus levels; and (4) calculating the arithmetic ranking values. We demonstrate the feasibility and superiority of the model, inviting experts to evaluate the WTTs against eight criteria. Finally, we conduct a series of comparative analyses and a sensitivity analysis. The model gives a thorough measure of WTTs across multiple criteria. The suitable WTT is different for small or medium towns, and big cities in developing or developed countries.